PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN DONGGALA - Saking, Indri Pratiwi (Katalogis, 2019)
This study aims to examine and analyze the Effect of Motivation on Employee Performance at the Department of Industry and Trade in Donggala Regency. To measure the motivation variable using David Mc Clelland's motivation theory, it covers the needs of achievement, the need for power, and the need for affiliation. Next to measure the performance variable using the performance theory by Kast and James, which covers the ability, effort, and opportunity. This research is a survey research with a quantitative approach. In data collection carried out using Observation, Questionnaire, Interview, and Documentation methods. Measurement of question items using a Likert scale and conducted Validation Test and Reliability Test on the research instrument. The data analysis of this study used Descriptive Analysis Technique and Inferential Analysis Technique with multiple linear regression model statistical techniques. The results of the study prove that the motivational effect simultaneously on the performance of employees at the Department of Industry and Trade in Donggala Regency is 0.881 or 88.1% with the category of Very Strong relationships. The effect of motivation partially on the performance of employees at the Department of Industry and Trade in Donggala Regency are variables X1, X2, and X3 with regression coefficients of each variable of 1.571, 1.968, and 0.532 this means that there is a significant influence between the need for achievement (X1 ) and the need for power (X2) on the performance of employees in the Department of Industry and Trade of Donggala Regency, while in the Vaiable of Needs for affiliation (X3) there is no significant effect on the performance of employees at the Donggala District Industry and Trade Office.